Molecular Characterization, 3D Model Analysis, and Expression Pattern of the CmUBC Gene Encoding the Melon Ubiquitin-Conjugating Enzyme Under Drought and Salt Stress Conditions - Baloglu, Mehmet Cengiz; Patir, Meliha Gorkem (Springer Science and Business Media LLC, 2013)
Ubiquitin-conjugating (UBC) enzyme is a key enzyme in ubiquitination. Here, we describe the cloning, characterization, and expression pattern of a novel gene, CmUBC, from a melon. Comparison of the deduced amino acid sequences allowed the identification of highly conserved motifs. Synteny analysis between Cucumis sativus L. and Arabidopsis demonstrated that homologs of several Cucumis UBC genes were found in corresponding syntenic blocks of Arabidopsis. The homology structure model of the CmUBC protein was constructed. UBCs from melon, yeast, and Arabidopsis were highly conserved in their three-dimensional folding. CmUBC was ubiquitously expressed in all melon tissues. Increased transcript levels of CmUBC were observed during drought and salinity stresses, which suggested that the expression of the CmUBC gene in melon plants is responsive to physiological water stress. These results suggested that the CmUBC gene might play an important role in the modulation of the ubiquitination pathway.
Keywords: Models, Molecular; Salinity; Base Sequence; Molecular Sequence Data; Droughts; Cucumis melo; Organ Specificity; Stress, Physiological; Ubiquitin-Conjugating Enzymes; Amino Acid Sequence; Phylogeny; Plant Proteins; 15. Life on land; 6. Clean water